Invisible Empire: Visual Culture, Embodied Spectacle, and Abu Ghraib. - Mirzoeff, Nicholas (Radical History Review)
Investigates the implications and visual-cultural effects of the recent revelations of U.S. treatment of Iraqi prisoners of war. Release of photographs taken in the Iraqi prison of Abu Ghraib which became public in April 2004; Lack of media attention on the issue during the subsequent U.S. presidential election campaign; Overview of allegations that prisoners were forced to enact same-sex erotic tableaux.